4 - African Diaspora and its Multiple Academic Affiliations: Curtailing Brain Drain in African Higher Education through Translocal Academic Engagemen - Langa, Patrício V. (Journal of Higher Education in Africa, 2022)
Scholars with multiple affiliations have become more visible by assuming their particular role in redressing global knowledge production inequities. This article explores multiple academic affiliations (MAAs) as one way to curb the effects of brain drain, particularly in African universities. It argues that MAAs, is an effective way to reverse the effects of brain drain and promote brain circulation and sharing. The article proposes the concept of translocal academic engagement (TLAE) as a form of international academic exchange and brain-sharing which is not limited to physical mobility (circulation) from one geographical location to the other, but which includes virtual exchange and knowledge-sharing through blended learning delivery methods, e-pedagogies and the use of digital communication technology platforms such as Communities of Practice. The article concludes by suggesting that MAAs, if properly managed, can be a success factor in TLAE activities, particularly in the age of Web 4.0, in mitigating or shifting currently dominating knowledge production flows. TLAE offers possibilities for a win-win situation of academic exchange between higher education institutions in emerging systems.